Encapsulation of N-doped carbon layer via in situ dopamine polymerization endows nanostructured NaTi2(PO4)3 with superior lithium storage performance. Issue 4 (March 2020) - Jiang, Zhen; Li, Yuehua; Han, Chao; Wu, Xianwen; He, Zhangxing; Zhu, Jing; Meng, Wei; Dai, Lei; Wang, Ling
Abstract: NaTi2 (PO4 )3 (NTP) anode with NASICON structure presents broad prospects for aqueous lithium ion battery. Nevertheless, its intrinsic poor conductivity and structure stability in aqueous solution restrict performance of materials. Herein, we used dopamine hydrochloride to fabricate N-doped carbon encapsulated NaTi2 (PO4 )3 nanosphere via in situ dopamine polymerization under different solution environments. Composites show obvious improvement on electrochemical performance compared with NTP. Additionally, utilization of Tris-buffer solution endows N-doped carbon encapsulated NaTi2 (PO4 )3 nanosphere with superior performance to those of composites acquired in other solution environments. Among all samples obtained in Tris-buffer, N-doped carbon encapsulated NaTi2 (PO4 )3 nanosphere with proper carbon layer shows superb electrochemical performance with discharge capacities of 127.5, 113.8, and 90.9 mA h g −1 at 0.2, 3.0, and 15C, respectively. Superb property may be due to the unique nanosphere structure. Nanospheres with better dispersion can shorten migration path of Li ions. Encapsulation of N-doped carbon layer improves stability in aqueous electrolyte and ameliorates electronic conductivity of materials. N doping enhances hydrophilicity and electronic conductivity, and also forms lots of defects on carbon layer, which contributes to Li ion intercalation/deintercalation. This work reveals that the combination of nanosphere and N-doped carbon layer offers a promising method to raise electrochemical performances of NaTi2 (PO4 )3 .